2019
DOI: 10.5005/jp-journals-10015-1637
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Various Bulk-fill Composite Resins in Class II MOD Cavity on Premolars: An In Vitro Study

Abstract: Background: Class II MOD cavity in maxillary premolar creates a specific challenge for the restoration material in terms of longevity and fracture resistance due to the anatomical shape of premolars that render them susceptible to fracture and the microleakage issue of composite restoration at the gingival margin of the proximal boxes. Bulk-fill composite was introduced to provide more strength and resistance and also to provide less polymerization shrinkage and better cure depth. With the advances in dental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…In this study, nonsignificant difference in FR values ( P > 0.05) was observed between the groups restored with bulk-fill Filtek and SonicFill 2 composites. This observation was aligned with other study reported in the literature [ 40 ]. This could be attributed to having nearly the same reduced polymerization shrinkage according to the manufacturer information (Filtek by 1.39%; SonicFill 2 by 1.6%) and also thanks to the specific modulation to reduce the polymerization shrinkage.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, nonsignificant difference in FR values ( P > 0.05) was observed between the groups restored with bulk-fill Filtek and SonicFill 2 composites. This observation was aligned with other study reported in the literature [ 40 ]. This could be attributed to having nearly the same reduced polymerization shrinkage according to the manufacturer information (Filtek by 1.39%; SonicFill 2 by 1.6%) and also thanks to the specific modulation to reduce the polymerization shrinkage.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, nonsignificant difference in FR values (P > 0.05) was observed between the groups restored with bulk-fill Filtek and SonicFill 2 composites. is observation was aligned with other study reported in the literature [40].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The shear strength test for tooth restoration is one way to measure the adhesion strength of the material 13 to the restored tooth structure besides the tensile strength test 14,15 . In this research the magnitude of force acceptable for composite resin restorations was measured when the restorations were detached from the tooth surface.…”
Section: Introductionmentioning
confidence: 99%